Outside Theater : Alliances That Shape Mexico - Day, Stuart A. (Stuart Alexander) (Book collections on Project MUSE., 2017)
Taking a cue from influential French philosopher Jacques Ranciere, who in The Emancipated Spectator rejects the idea of the passive, ignorant, duped spectators in need of instruction to become active, Stuart A. Day's goal in Outside Theater is to highlight written words and performances that exemplify effective strategies, past and present, to reveal and promote civic engagement, to provoke disruptions, or to highlight fissures--and opportunities--in oppressive social structures. Through the study of one or two primary models per chapter, as well as multiple examples in the introduction and conclusion, Day presents Mexican plays from 1905 to 2015, including the 2010 Mexico City performance of Zoot Suit by Chicano playwright Luis Valdez. Using these plays, Day explores the concept of "outside theater," where people or groups translate the tools of the theatrical trade to a different stage, outside the walls of the theater, and play the part of fictional or real life Celestinas--matchmakers who unite seemingly disparate entities to promote social awareness and social action by working the borders between life and art. Each work in this innovative analysis reveals productive social connections that, with the help of crucial artistic alliances, contradict the perception that art is somehow secondary to or disconnected from the public sphere of influence and the struggles of everyday life. With this book, Day shows that Mexican theater can and does bolster civil society and thus the country's fragile democracy.